Deposit-online: challenges for it development in Spain - Santos de Paz, Lourdes (Revista General de Información y Documentación, 2018)
The study aims to show the challenges facing by conservative institutions and the strategies that must be proposed to carry out the preservation of the cultural heritage that is produced in an intangible way in the Spanish territory. The need to preserve the documents currently produced in an intangible way has caused a change in the process of management of the Legal Deposit so that custody institutions have to face new challenges in order to carry out the necessary development in Spain regarding legislation from the Royal Decree 635/2015 of 10 July that comes to develop Law 23/2011 of Legal Deposit.
Keywords: Archiving of the web; Digital collections; Digital preservation; Online Legal Deposit; Spanish digital Heritage